2016
DOI: 10.1002/celc.201600095
|View full text |Cite
|
Sign up to set email alerts
|

Smart Windows Prepared from Bombyx mori Silk

Abstract: We introduce a bioinspired strategy for the synthesis of green polymer electrolytes (PEs) that relies on the use of silk fibroin (SF). The two series of PEs prepared, doped with lithium bis(trifluoromethanesulfonyl)imide or lithium tetrafluoroborate and incorporating glycerol, exhibited outstanding filmogenic properties, very high transparency, and suitable adhesion to glass substrates. Despite their poor ionic conductivity, the SF‐based films were employed in the construction of glass/ITO/WO3/PE/CeO2–TiO2/ITO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 107 publications
2
29
0
Order By: Relevance
“…The rather unusual behavior observed leads us to suppose that in both samples something occurred in the 40–80 °C temperature range. Other authors [43] reported similar perturbations in the ionic conductivity behavior of the natural polymers‐based electrolytes with the increase of temperature. A competition between different factors such as the number of charge carriers, the mobility of the charge carriers, the recombination and/or aggregation of components, determines the final ionic conductivity of the electrolyte.…”
Section: Ionic Conductivitysupporting
confidence: 57%
“…The rather unusual behavior observed leads us to suppose that in both samples something occurred in the 40–80 °C temperature range. Other authors [43] reported similar perturbations in the ionic conductivity behavior of the natural polymers‐based electrolytes with the increase of temperature. A competition between different factors such as the number of charge carriers, the mobility of the charge carriers, the recombination and/or aggregation of components, determines the final ionic conductivity of the electrolyte.…”
Section: Ionic Conductivitysupporting
confidence: 57%
“…In spite of the very high CE values produced, the ECD@LiTrif-[Er(tta) 3 (H 2 O) 2 ] device needs further improvements so that the ∆T and ∆OD values are substantially increased. At present, the addition of the same salt/complex mixture to cheap, abundant, and benign natural host polymers is being considered (e.g., proteins [39] or polysaccharides [24]) is being considered.…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75] This is in the condition that solid or gel electrolytes were most popular in research performed on ECDs. [69,76] Solid electrolytes are often polymeric consisting of a polymer as host, a salt or ionic liquid, solvents (acid or water), and additives such as glycerol as a plasticizer. The variety of available polymers and especially natural, environmentally friendly polymers, which are usable in devices, has increased the appealing of research in the field of SPEs.…”
Section: Electrolytementioning
confidence: 99%